Age‐Period‐Cohort approaches to back‐calculation of cancer incidence rate. (26th February 2015) - Oh, Cheongeun; Holford, Theodore R.
<x xml:space="preserve">Abstract</x> A compartment model for cancer incidence and mortality is developed in which healthy subjects may develop cancer and subsequently die of cancer or another cause. In order to adequately represent the experience of a defined population, it is also necessary to allow for subjects who are diagnosed at death, as well as subjects who migrate and are subsequently lost to follow‐up. Expressions are derived for the number of cancer deaths as a function of the number of incidence cases and vice versa, which allows for the use of mortality statistics to obtain estimates of incidence using survival information. In addition, the model can be used to obtain estimates of cancer prevalence, which is useful for health care planning. The method is illustrated using data on lung cancer among males in Connecticut. Copyright © 2015 John Wiley & Sons, Ltd.